MODEL POLICY DESIGN FOR THE BEEF CATTLE RANCH DEVELOPMENT IN SOUTH SULAWESI - Achmad, Machmud; Hartoyo, Sri; Arifin, Bustanul; Didu, Muhammad Said (European Scientific Journal, ESJ, 2013)
The main objective of this study is to examine the existing condition of the ranchers, namely economic and social characteristics in related to the development of beef cattle. It examines factors that influences of policies on developing cattle beef and while designing integrated planning systems in South Sulawesi. The method for this study includes qualitative and quantitative approaches using survey method to obtain primary data. Data were analyzed and presented in the .form of descriptive tables graphs with analytical tools policy. Results were obtained .from choices of recommendations, elaborated in the form of strategy and policy implications based on expert opinions (expert judgment), Internal and External Matrices with the SWOT analysis and the QSPM. Results show that current position for beef cattle in South Sulawesi is in grow and build. Therefore, by analyzing all the factors from SWOT, four strategies were developed to support the beef cattle. Using the QSPM, results further suggests that the best strategy to develop is the first strategy. This strategy recommends that in order to develop the beef cattle in South Sulawesi, there should be an integrating system between the beef cattle rancher and crop (rice and corn). The strategy also implies that in order to achieve this goal, technology improvement and innovation play important keys, specially technology for the feed processing system.